The influence of project-based Learning on nursing students' core competencies : a case study in China - Gong, Ran (2017)
Gong, Ran. 2017. The Influence of Project-based Learning on Nursing Students’ Core Competencies: A case study in China. Master's Thesis in Education. University of Jyväskylä. Department of Education.